MODERASI BERAGAMA DALAM BINGKAI SASTRA: EKSPLORASI PADA LIRIK LAGU KARYA RHOMA IRAMA - Manshur, Ali; Ma’arif, Syamsul (International Conference on Humanity Education and Society (ICHES), 2024)
This research discusses the exploration of Rhoma Irama's song lyrics which contain messages of religious moderation. This is the first and only research on religious moderation messages in Rhoma Irama's song lyrics. The aim of this research is to describe the lyrics of songs by Rhoma Irama as one of the reinforcements for the idea of ​​religious moderation initiated by the Indonesian Ministry of Religion as well as becoming a strategic issue in the era of President Jokowi's leadership. The method used in this research is qualitative description using skillful free-involved listening techniques. From the results of this research, regarding the exploration of song lyrics by Rhoma Irama which contain messages or values ​​strengthening religious moderation, ten song works were found.